STRATEGI PENGEMBANGAN PALA DI DESA PAISUBATU KECAMATAN BUKO KABUPATEN BANGGAI KEPULAUAN - Mudin Mudin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
This is a descriptive qualitative research with aims were to analyze the development strategy of nutmeg farming in Paisubatu village Buko sub district of Banggai Kepulauan District. The research location was purposively determined where 25 sample respondents was selected according to a simple random tehnique.  Data obtained was analyzed using SWOT analysis.  The strategy found for developing the nutmeg farming in Paisubatu village Buko sub district of Banggai Kepulauan district were as follows: (1) establishing cooperation with both government and private sector, (2) improving technology for nutmeg added value, (3) establishing relationship with related government institution to promote the nutmeg commodity either locally or internationally, (4) involving in the trainings performed by related government institution for processing of nutmeg products, (5) creating pests and diseases protection house to overcome both pest and disease attack on the nutmeg plants, (6) training the farmers for marketing, conducting and developing technology, (7) taking part in the activities running by the Agriculture and Plantation Office in order to control pests and diseases on the nutmeg plants, (8) optimizing rersources and markets, and (9) establishing cooperation with farmer groups that have more advance tecnology. Keywords : Development Strategy, IFE and EFE Matrix, Nutmeg, and SWOT.